The SHA.LIN renal stone scoring system for predicting stone-free status and postoperative outcomes after percutaneous nephrolithotomy - Jia, Lei; Wang, Jiuyi; Wang, Tao; Wang, Shaogang; Li, Qiang; Wang, Qinzhang; Liu, Jihong; Zeng, Kai (Frontiers in Surgery, 2025)
ObjectiveTo introduce a novel renal stone scoring system (SHA.LIN) for percutaneous nephrolithotomy (PCNL) and to compare the predictive power of the SHA.LIN scoring system vs. the Guy's stone score and S.T.O.N.E. scoring system for postoperative outcomes.MethodsSix reproducible parameters available from preoperative computed tomography (CT) data were measured: stone burden (S), hydronephrosis (H), anatomical distribution (A), length of tract (L), indicator of CT (I), and number of involved calyces (N). Data from patients who underwent PCNL between May 2019 and January 2023 were retrospectively reviewed. Correlations between scores from the 3 systems (i.e., SHA.LIN, STONE, and Guy's) and stone-free status (SFS), hemoglobin change, estimated blood loss (EBL), operative time (OT), and postoperative length of hospital stay (PLOS) were evaluated using standard statistical methods.ResultsThe overall stone-free rate was 69.7% (248/356), and complications occurred in 111 (30.9%) patients. Patients were divided into 2 groups (stone-free vs. non-stone-free), with median (IQR) scores as follows: Guy's, 2 (1–2) vs. 3 (2–3); S.T.O.N.E., 6 (6–8) vs. 8 (7–9.5); and SHA.LIN, 7 (7–9) vs. 11 (10–12.5), respectively (p < 0.001 for all). Univariate regression analysis revealed that the three scoring systems were significantly associated with SFS and OT, although none were significantly correlated with PLOS. EBL and hemoglobin change were significantly correlated with the SHA.LIN score. Multivariate regression analysis revealed that the three scoring systems were significantly associated with SFS. EBL and hemoglobin change were significantly correlated with the SHA.LIN score. Receiver operating characteristic (ROC) curve analysis revealed that the three scoring systems demonstrated comparable predictive accuracy for SFS and complications, with SHA.LIN having the highest area under the ROC curve (AUC) (0.852 and 0.774, respectively). Analysis of the respective AUCs revealed that the SHA.LIN score more accurately predicted EBL (AUC 0.807) than the other 2 scoring systems.ConclusionThe SHA.LIN scoring system accurately predicted postoperative outcomes of PCNL and demonstrated potential as an adjuvant tool for surgical planning. The three scoring systems demonstrated strong associations with SFS, in addition, the SHA.LIN score was also significantly associated with the risk of surgical bleeding.